2019
DOI: 10.1155/2019/8727925
|View full text |Cite
|
Sign up to set email alerts
|

Potential Involvement of BIRC5 in Maintaining Pluripotency and Cell Differentiation of Human Stem Cells

Abstract: The BIRC5 gene encodes a survivin protein belonging to class III of inhibitors of apoptosis, IAP. This protein serves a dual role. First, it regulates cell death, and second, it is an important regulator of mitosis progression, although its physiological regulatory function has not been fully understood. Many studies have shown and confirmed that survivin is practically absent in mature tissues in nature, while its overexpression has been reported in many cancerous tissues. There is little information about th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 54 publications
3
24
0
Order By: Relevance
“…(Life Technologies). Detailed procedures for the cells isolation, reverse transcription and real time PCR reactions have been described in our previous work, where we showed that the studied hematopoietic stem cells of peripheral blood and healthy bone marrow cells express the high level of BIRC5 gene expression, which confirms native nature of the tested hematopoetic stem cells [27].…”
Section: Qpcr Reactionsupporting
confidence: 71%
“…(Life Technologies). Detailed procedures for the cells isolation, reverse transcription and real time PCR reactions have been described in our previous work, where we showed that the studied hematopoietic stem cells of peripheral blood and healthy bone marrow cells express the high level of BIRC5 gene expression, which confirms native nature of the tested hematopoetic stem cells [27].…”
Section: Qpcr Reactionsupporting
confidence: 71%
“…Moreover, in the light of our previous research [34] in which we suggested that BIRC5 is involved in maintaining the state of pluripotency and stem cell differentiation, the higher BIRC5 expression demonstrated in the current study may indicate a more stem cell-like character of the isolated cells, their greater potential for differentiation, and thus better clinical utility of stem cells obtained from the umbilical cord from women after a natural childbirth.…”
Section: The Effect Of the Methods Of Delivery On The Expression Of Gesupporting
confidence: 61%
“…Mesenchymal stem cells were isolated from the umbilical cord Wharton's jelly using the explant method [34]. To demonstrate the stem cell character of the isolated cells, cytometric analysis was performed and the presence of CD90 and CD105 surface antigens was demonstrated in the majority of the population studied [35].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Monoclonal fluorescently labeled mouse anti-human CD90 PC5-labeled by Beckman Coulter and mouse anti-human CD105 PE-labeled by Beckman Coulter were used to assess the phenotype of the [14]. Detailed procedures for the isolation of reverse PCR transcription and real-time PCR reactions have been described in our work [15]. The statistical analysis was performed using the Statistica v. 13.0 software.…”
Section: Cytometric Analysismentioning
confidence: 99%